x^2-10-4x-11=0

Simple and best practice solution for x^2-10-4x-11=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x^2-10-4x-11=0 equation:


Simplifying
x2 + -10 + -4x + -11 = 0

Reorder the terms:
-10 + -11 + -4x + x2 = 0

Combine like terms: -10 + -11 = -21
-21 + -4x + x2 = 0

Solving
-21 + -4x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -1x)(7 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7

Solution

x = {-3, 7}

You can always share this solution

See similar equations:

| 5x^3+(2x-12)=1 | | m^2-6m+8=0 | | m^2+10m+9=0 | | m^2+5m+6=0 | | 5x^2+10x+5=180 | | 6(1+8x^3)=9 | | x^3+6x^2=4x+24 | | 5x^2-7x+2=0 | | 2x^2-11x+15=0 | | 4x^2=12x | | 8x^2=72x | | 2x^2-2=-5x-1 | | 0=3x^2-5x-9 | | 3x^2-6x+9=0 | | 3q^2+16=-19q | | (-2x^2+3y^3)+(6x-5)=0 | | 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v |

Equations solver categories